Rational Choice Penjual Dan Pembeli Dalam Perdagangan Barang Counterfeit Di Pasar Taman Puring, Jakarta - Monica Margaret; Alrizq Athallah Sulung Esa (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The term counterfeit goods appears in the use of the brand field which refers to certainactions in seeking profit by trading, either producing or selling counterfeit, imitation orcounterfeit goods. The labeling of counterfeit goods is taken from the way the goods areproduced, namely by counterfeiting (forgery). This research is descriptive qualitative whichexplains the factors and causes behind sellers and buyers trading counterfeit goods which areanalyzed with Rational Choice Theory which describes that criminals are seen as rational partiesin making decisions and actions, as well as when buyers choose rational choice in buyingcounterfeit goods. In Indonesia, the business of counterfeit goods is growing in line with thelifestyle of the people in general. The research was conducted at Taman Puring Market, SouthJakarta, which is the location of a large number of counterfeit goods trade. By obtaining datafrom several sources who are sellers and buyers of counterfeit goods, it is found that there aremany factors that influence the occurrence of counterfeit goods trade, namely, price factors,quality factors, trend factors, needs factors, place reference factors and self-awareness factors.There are also many causes that can be measured from the point of view of Rational ChoiceTheory, namely profit, means, control and punishment.